TikTok Versus Instagram Reels: Platform for Promotional Content for Online Fashion Business (Case Study on Online Fashion Brand Marasoe) - Alfarisi Alfurqon, Farhan (Educationist: Journal of Educational and Cultural Studies, 2023)
Social media has had a drastically increased usage rate since the COVID-19 pandemic required everyone to stay at home. The number of active social media users is very large, namely as many as 196.7 million users (Jatmiko, 2020). Many people are starting to socialize through social media. But not only that, economic activity can also take place through social media. Many new businessmen have sprung up on social media to promote their products. Social media that is widely used for doing business is Tiktok and Instagram. Tiktok and Instagram have become very popular so that they have enormous opportunities for business people. This makes business people need to adjust how to promote the right way on each platform and continue to look for opportunities from each platform. Therefore, the authors compiled a study entitled Tiktok vs Instagram Reels: Online Fashion Business Promotion Media (Case Study on Online Fashion Brand Marasoe). This study aims to answer several problem formulations such as what are the opportunities for Tiktok as a medium for promoting the Marasoe online fashion business, what are the opportunities for Instagram Reels as a media for promoting the Marasoe online fashion business, and how to determine and adjust appropriate promotional content on each of the Tiktok and Instagram Reels platforms. for the Marasoe online fashion business. The results of this study are that the Tiktok and Instagram Reels platforms have the same opportunity to match the Marasoe target market. The form of content uploaded on Tiktok and Instagram Reels has a slight difference, so it can be adjusted accordingly. Tiktok viewers tend to like videos that are entertainment and are given discounts/low prices when it comes to hard selling. Meanwhile, Instagram Reels viewers tend to like aesthetic and exclusive content.